Reconsidering The President's Insult Scandal: A Constitutional Critique Of The New Criminal Code - Yusuf, Ismail; Ismail, Dian Ekawaty; Imran, Suitno Yutye (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
Law Number 1 of 2023 concerning the Criminal Code (KUHP) is a milestone in the long-awaited national criminal law reform. However, the reintroduction of articles regulating the offense of violating the President and Vice President in the new Criminal Code raises serious concerns about the consistency of the Indonesian legal system with constitutional principles. One of the main highlights is the inconsistency with the Constitutional Court Decision Number 013-022/PUU-IV/2006, which previously removed similar articles because they were considered to be the right to freedom of expression and equality before the law. This article examines these provisions through a normative legal approach with a focus on the principle of equality before the law and strengthening it against the constitutional rights of citizens. The results of the study show that the special offense of insulting the president not only threatens freedom of expression but also creates inequality in legal treatment that has the potential to perpetuate the symbolism of power that is inconsistent with the democratic system of the republic. Law enforcement against violations should be carried out through general provisions in the Criminal Code that apply to all citizens without discrimination. Therefore, there needs to be an evaluation and harmonization of the norms in the new Criminal Code so that they are in line with the principles of a state based on law that upholds justice, equal rights, and respect for human rights.